AN ANALYSIS OF STUDENTS’ ERRORS IN USING CONDITIONAL SENTENCE AT ELEVENTH GRADES STUDENTS OF SMA MUHAMMADIYAH 11 PADANDSIDIMPUAN IN THE ACADEMIC YEAR 2020/2021 - irfan sandy harahap (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract: This research was conducted at the eleventh grade SMA Muhammadiyah11 in 2020/2021 academic year with respondent 20 students. The purpose of this research was to find: 1) to know what the students' error in using conditional sentence, 2) why students made errors in using conditional sentence. This research use mix method. The data were collected by test and interview. Triangulation was used in checking trustworthiness. The results of this study are 1) the result of students test in conditional sentence is enough, with percentage the correct is 64% and the errors is 36%, 2). Students errors in using conditional sentence, includes: 19% errors of addition, 18% error of omission, 56% error of misformation, and 7% error in misordering. The researcher concludes that from the calculation of the data, misformation errors are the most common error made by the students. The writer found, there are two main causes of the students’ errors in using conditional sentence. The first is the students don’t understand and inability in using past form. The second is the inability of the students in differentiating between conditional sentence type 1, type2, and type 3. Keywords: students’ errors, conditional sentence